Pengelolaan Digital Public Relations Pada Konten Edukatif di Akun Instagram @dishut_jabar - Siti Nur Anggraeni Kuswanti; Rizki Surya Tawaqal; Detya Wiryany (Buana Komunikasi (Jurnal Penelitian dan Studi Ilmu Komunikasi), 2025)
This study examines the strategic management of Digital Public Relations through educational content on the Instagram account @dishut_jabar. Employing a descriptive qualitative approach, data were collected through semi-structured interviews, direct observation, content analysis, and documentation. The findings reveal that digital public relations are managed systematically through content planning, visually engaging designs, communicative language, and interactive formats such as infographics, quizzes, and short-form videos. Two-way communication in the comment section facilitates dialogic interaction, encourages public discussion, and supports participation in environmental initiatives such as Jumat Menanam, despite challenges related to audience engagement and platform algorithms. These practices reflect the principles of Kent and Taylor’s Dialogic Public Relations Theory, including mutuality, propinquity, empathy, and risk. Overall, the study demonstrates how dialogic and educational social media communication can enhance public engagement and participation in government-led environmental conservation efforts.